A Hermeneutic Study of the Ethical Use of Technology in Arabic Language Education: A Perspective of Qur'anic Verses - Wisnu Raharjo; Rokhani Rokhani; Anis Malik Toha (Yayasan Pendidikan Haiba Nasywa, 2025)
This research project takes a Qur'anic hermeneutic approach to examine the ethical use of technology in Arabic language education. The study aims to formulate ethical guidelines aligned with sharia objectives by analysing relevant Qur'anic verses. A qualitative literature review is employed, combining Qur'anic text analysis, contextual interpretation and supporting studies on hermeneutics and technology ethics. The findings reveal that values such as honesty (Al-An'am: 152), justice (An-Nisa': 135) and balance (Al-Qasas: 77) form the basis of the ethical use of technology. Hermeneutics enables the dynamic interpretation of sacred texts in order to address contemporary challenges, such as the instant nature of modern culture or the access gaps relating to technology. The research also emphasises that technology should be used to strengthen spiritual values rather than merely as a technical tool. Referring to the maqashid of sharia, the resulting ethical guidelines aim to educate the ummah (Fatir 28) and strengthen understanding of the Qur'an through Arabic. The study's contribution is that Arabic education in the digital era can be inclusive, equitable and grounded in scientific integrity.